The evidential basis of linguistic argumentation - Kertész, András; Rákosi, Csilla (Studies in language companion series, 2014)
This chapter provides a survey about the most frequent methods of inconsistency resolution in Optimality Theory. With the help of the p-model, inconsistencies in OT are divided into two main groups. The first group includes conflicts that are deemed to be fatal and are solved usually by the modification of the theory: namely, clashes between "linguistic data" (acceptability judgements) and applications of the model (results of the evaluation procedure). The second group consists of conflicts that are, in contrast, tolerable in the view of OT theorists: inconsistencies between constraints and t